Patient-centered care at Joslin: Reflections of a mirror - Madden, Paul B. (Journal of Social Health and Diabetes, 2014)
This personal communication describes the practical aspects of patient-centered care (PCC), as viewed by a person with diabetes, who is also a diabetes educator. He describes his encounters with two leading diabetologists, who practiced the real essence of PCC. The author also explains the impact these patient-centered doctors had on him, and how it has shaped his personal as well as professional life, over the past half century.
Keywords: India; patient empowerment; patient values; shared decision making; USA